A study and analysis of the level of impact of regulatory control mechanisms on the sustainability of quality in accounting profits in Saudi Banks - Alnor, Nasareldeen Hamed Ahmed; Eltahir, Ibrahim Ahmed Elamin; Adam, Salih Hamid; Taha, Mozamil Awad; Al-Matari, Ebrahim Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
When evaluating an organization's performance and financial health, the quality of earnings is a crucial consideration. This study examines how regulatory oversight mechanisms, such as the audit committee, perceive risks in the sustainability of accounting earnings quality in Saudi banks. In order to identify and stop earnings manipulation, audit committees supervise financial statements, internal controls, and external audits. Risk committees, meanwhile, find and eliminate operational and financial hazards that might skew reported profits. The correlation coefficient was used to calculate the relationship between the independent variable and the dependent variable. The coefficient of determination was also used to calculate the effect or contribution of the independent variable to the dependent variable. The study's findings indicated a statistically significant correlation between committee independence (ACIN), size (CSIZE), and number of independent directors (ACSIZE) and earnings quality (PRQU). ACSIZE had a favorable impact, indicating that having more independent directors improves the accuracy of financial reporting. Given that the ACIN coefficient was negative, it is probable that excessive independence in the absence of sufficient control mechanisms prevents earnings quality from improving consistently. Policymakers, business executives, and investors can benefit from the study's recommendations for bolstering audit and risk committee operations to improve overall company governance and profits quality.